Production of potato nuggets in Barangay Libis, Binangonan, Rizal - Pereira, Huan Carlos B.; Ynares, Jonas D. (2025)
This study determines the viability of producing a potato nuggets in Barangay Libis, Binangonan, Rizal. The business seeks to provide a healthy, affordable, and delicious snack option while contributing to local economic development and sustainable practices. The primary objective is to create a nutritious, plant-based snack by using locally sourced potatoes, herbs, and spices. This strategy meets the growing consumer demand for healthier snack options while encouraging the community to adopt better eating habits. The product will be marketed as plant-based, low in fat, and rich in essential nutrients. Social media campaigns, partnerships, and educational content will highlight the product's health benefits, motivating consumers to choose healthier snacks Starting as a sole proprietorship allows the business to maintain full control over product quality and operations. fostering economic growth within the community. A streamlined production process, coupled with strict quality control, ensures consistent product excellence. Sustainable practices, such as eco-friendly packaging and waste minimization, will be implemented to align with the company's environmental goals The marketing strategy will emphasize the products affordability, quality, and health benefits. Digital marketing through platforms like Facebook and Instagram will target health-conscious consumers and younger demographics. Collaborations with local influencers will build trust and broaden the product's reach. Additionally, in-store promotions and participation in community events will create direct engagement opportunities with potential customers. This comprehensive marketing strategy is designed to build brand awareness and foster customer loyalty. Affordability is a core principle of this business. By pricing the potato nuggets at P100 per pack, the product remains affordable to a wide range of consumers without compromising quality. The use of locally sourced ingredients helps reduce production costs, enabling competitive pricing. The business may rise the price in the future depending on the economic climate With an initial capital investment of P50,000, the business anticipates consistent revenue growth due to increasing market demand and scalable operations. Projections suggest that sales will double annually, reaching P1,175,801 pesos in revenue by the fifth year. It is expected that the business will sel The Production of Potato Nuggets in Barangay Libis, Binangonan, Rizal demonstrates strong financial viability. The initial P50,000 investment is projected to be recovered within a few years, ensuring a quick payback period. The business shows high profitability, with ROI reaching 111.04% in 2024 before stabilizing at 53.32% by 2027. Gross profit margins are expociod lo grow from 55% in 2023 lo 63% in 2027, while net profit margins rise from 15.76% to 50.91% over the same period with cost-effective operations, elficient marketing, and increasing demand, the business is positioned for long-term growth, making it a promising investment. Cost-efficient production, effective marketing, and reinvestment in operations will support profitability and long-term business expansion. Profit margins will be closely monitored to ensure sustainable growth while maintaining product quality and affordability. Establishing a potato nugget production business in Barangay Libis presents a viable and promising opportunity. The business aligns with the growing demand for The Establishment of Potato Nuggets Business in Barangay Libis, Binangonan, Rizal will give a big boost to the improving local business agenda in our place. More likely the students and passers-by will enjoy the palatable taste of the product. Healthy, affordable snack options while fostering local economic growth and sustainability. By supporting the local potato farmer /supplier chhe agricultural products with its tagline (Fresh from the farm) .
Undergraduate Feasibility Study
Includes bibliographical references